2012
DOI: 10.1152/ajpcell.00177.2011
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular chloride regulation of Kv2.1, contributor to the major outward Kv current in mammalian outer hair cells

Abstract: Outer hair cells (OHC) function as both receptors and effectors in providing a boost to auditory reception. Amplification is driven by the motor protein prestin, which is under anionic control. Interestingly, we now find that the major, 4-AP-sensitive, outward K+ current of the OHC ( IK) is also sensitive to Cl−, although, in contrast to prestin, extracellularly. IK is inhibited by reducing extracellular Cl− levels, with a linear dependence of 0.4%/mM. Other voltage-dependent K+ (Kv) channel conductances in su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…Cochlear sections from WT and Kv2.2KO animals were treated with an identical protocol and then Kv2.2 and Kv2.1 immunohistochemistry was performed. Kv2.1 immunoreactivity was observed, consistent with previous reports (Li et al, 2012), but no specific Kv2.2 staining (Fig.3c, 3d) was observed in the hair cells or in the spiral ganglion (not shown). In conjunction with the positive control from the brainstem, we conclude that there is no Kv2.2 expressed in the cochlea and hence any changes in hearing associated with the absence of Kv2.2, must reflect a central rather than a peripheral location of this channel.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Cochlear sections from WT and Kv2.2KO animals were treated with an identical protocol and then Kv2.2 and Kv2.1 immunohistochemistry was performed. Kv2.1 immunoreactivity was observed, consistent with previous reports (Li et al, 2012), but no specific Kv2.2 staining (Fig.3c, 3d) was observed in the hair cells or in the spiral ganglion (not shown). In conjunction with the positive control from the brainstem, we conclude that there is no Kv2.2 expressed in the cochlea and hence any changes in hearing associated with the absence of Kv2.2, must reflect a central rather than a peripheral location of this channel.…”
Section: Resultssupporting
confidence: 92%
“…The Kv2 potassium channel family has two members: Kv2.1 and Kv2.2; the former is highly expressed in the hippocampus and neocortex (Du et al, 2000; Guan et al, 2007) and hair cells (Li et al, 2012) where Kv2.1 containing channels are considered the dominant delayed rectifiers and responsible for action potential repolarization. Kv2.2 has a much more restricted expression profile, and in the auditory brainstem is expressed exclusively in the initial segment of the MNTB neurons and in VNTB neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The 4-Ap-sensitive outward rectifying K ϩ channel (K v ) is one of the two major K ϩ channels in the outer hair cell (OHC) and has several kinetic components when activated by a depolarizing pulse (59). The channel is activated by [Cl Ϫ ] out with a shallow linear dependence on [Cl Ϫ ] out between 5 and 150 mM (Fig.…”
Section: Channels Regulated By [Cl ؊ ]Outmentioning
confidence: 99%
“…The channel is activated by [Cl Ϫ ] out with a shallow linear dependence on [Cl Ϫ ] out between 5 and 150 mM (Fig. 2B), with [Cl Ϫ ] out differentially affecting each of its kinetic components (59). Topical expression of various outward rectifying channels has shown that K v 2.1 and K v 1.5 are activated by [Cl Ϫ ] out with the properties of K v 2.1 most resembling the K ϩ channel of OHC and indicating that K v 2.1 accounts for the [Cl Ϫ ] out sensitivity of OHC (59).…”
Section: Channels Regulated By [Cl ؊ ]Outmentioning
confidence: 99%
“…Although the chloride-mediated regulation of a few soluble proteins has been defined at both a biochemical and structural level, for example α-amylase and hemoglobin (13, 15), how changes in chloride concentration regulate other proteins including those in cellular membranes is unknown. For example, chloride regulates the voltage-gated potassium channel KCNB1, increasing the K + current as a function of chloride in patch-clamp studies (16). The chloride-dependent Na + /H + exchanger (Cl− NHE) is activated by chloride, as determined by intracellular pH measurements on exchanger-transfected cells (17).…”
Section: Introductionmentioning
confidence: 99%